2005
DOI: 10.1681/asn.2004100820
|View full text |Cite
|
Sign up to set email alerts
|

Viral Double-Stranded RNA Aggravates Lupus Nephritis through Toll-Like Receptor 3 on Glomerular Mesangial Cells and Antigen-Presenting Cells

Abstract: How viral infections trigger autoimmunity is poorly understood. A role for Toll-like receptor 3 (TLR3) was hypothesized in this context as viral double-stranded RNA (dsRNA) activates dendritic cells to secrete type I interferons and cytokines that are known to be associated with the disease activity in systemic lupus erythematosus (SLE). Immunostaining of nephritic kidney sections of autoimmune MRL lpr/lpr mice revealed TLR3 expression in infiltrating antigen-presenting cells as well as in glomerular mesangial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(190 citation statements)
references
References 46 publications
(54 reference statements)
6
179
1
3
Order By: Relevance
“…A study by Patole et al 25 investigated the effect of polyI:C, an IFNab-inducing component resembling viral dsRNA, on kidney cells. They found that mesangial cells expressed the dsRNA receptor toll-like receptor-3 and responded specifically to polyI:C treatment by producing chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Patole et al 25 investigated the effect of polyI:C, an IFNab-inducing component resembling viral dsRNA, on kidney cells. They found that mesangial cells expressed the dsRNA receptor toll-like receptor-3 and responded specifically to polyI:C treatment by producing chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In models of chronic glomerular disease, viral doublestranded RNA, a known TLR3 ligand, and bacterial DNA, a TLR9 ligand, have been shown to aggravate lupus nephritis (37,38). Bacterial DNA also has been shown to aggravate horse apoferritin-induced glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…10 and Table 1). TLR3 showed the most increase and is shown to aggravate lupus nephritis (51). To examine the presence of TLR proteins and their association with Fc␥RIIIa in CD4 ϩ T-cells, we stained P116 cells after co-stimulation with ICsϩC5b-9.…”
Section: C) Both Isotype Control and Cells Alone Did Not Show Thymidmentioning
confidence: 99%